Negative interpretation bias and emotional responses to positive contexts - Emily Gawlik; Karin Coifman (PLoS ONE, 2026)
Negative interpretation bias, the tendency to interpret ambiguous situations as negative or threatening, is associated with reports of intense and more frequent negative affect. However, there is a relative paucity of work seeking to determine whether this cognitive bias might account for individual differences in affective responses to positive content. Given the wealth of benefits associated with positive emotional experiences, such as greater psychological wellbeing and better physical health, this investigation tested the influence of negative interpretation bias on emotion responses to evocative positive film clips as positive emotion-eliciting contexts. Negative interpretation bias was indexed using a novel word matching task. In each investigation, careful consideration of dispositional or trait-level influence on interpretation bias (i.e., dispositional negativity) was considered. Investigations conducted across three samples of college students at a large, Midwestern public university reveal complexity to this question: in one study, a small significant indirect effect of negative interpretation bias on the association between dispositional negativity and self-reported affect following positive emotionally-evocative films was found, while in the two subsequent studies, no significant mediation was found. Certain contextual factors, such as the explicit or discrete nature of the clip presentation as well as more stable tendencies toward positive emotional responsivity and the capacity to self-report emotional experiences, appear to be important. Finally, the novel task was found to be reliable and demonstrated convergent validity with established indicators. Future work should continue to clarify the conditions under which negative interpretation bias may influence responses to positive emotional contexts, given the importance of positive emotionality for lifelong physical and mental health.